Creative and Innovative Education-Based Free Illiteracy Cottage: An Effoert to Eradicate Illiteracy Among Suku Anak Dalam in Batanghari Regency - reli handayani; Saharudin Saharudin; Siti Amanah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Suku Anak Dalam (SAD) in Kotoboyo Village, Batanghari Regency is an isolated community group that is currently in a transition phase towards modern life. Guided Village Service activities are carried out to bridge the transition process by providing creative and innovative education-based learning facilities to improve their quality of life. This service is aimed to foster and teach the importance of science by developing the ability to read and write. Therefore, this service establishes the illiterate-free cottage and education group as a means of creative and innovative learning. The learning process involves creating appropriate teaching aids and modules so they can be easily accepted by the target children. In the end, this creative and innovative education-based learning succeeded in increasing cognitive knowledge and learning motivation. Foster children who initially did not know letters and numbers become able to recognize and even write letters and numbers even though they are still in the initial stages. For families and parents of Suku Anak Dalam, the service team finally managed to direct them to actively participate in learning activities and have insight into healthy and clean lives. Many children have also understood the importance of hygiene so that the lives of the inner tribe children are expected to be better.